Microfluidic-enabled nanomedicine: a comprehensive review of recent advances and translational potential - Lye, Fiona Sze Nee; Loo, Yan Shan; Mat Azmi, Intan Diana; Lee, Choy Sin; Zahid, N. Idayu; Madheswaran, Thiagarajan (Springer Science and Business Media Deutschland GmbH, 2025)
Microfluidic technology is designed for the liquid handling and manipulation of fluids and materials at a small scale. This technology offers distinct advantages that address the limitations of conventional methods such as precision control, reproducibility, efficiency, and rapid processing. These advantages signify a paradigm shift in the field of biomedical and pharmaceutical research, particularly in the preparation of nanomedicines. This review briefly introduces microfluidics along with its principles and fundamentals, including the key components, different types of microfluidic mixing mechanisms, and materials used in microfluidic devices. It also comprises a detailed discussion of the benefits and challenges of using microfluidics in preparing nanoformulations (such as lipid-based, polymer-based, inorganic-based, and hybrid-based) and biomedical applications. This review also discusses the advancement of microfluidic and nanomedicine preparation, such as modular microfluidics, digital microfluidics, three-dimensional (3D) printed chips, automated microfluidics, artificial intelligence (AI), and healthcare wearable devices (HWDs). The review concludes by encouraging cooperation between multiple parties for the success of nanomedicine and offering better patient care to the public.